ANALISIS TINGKAT PEMAHAMAN MAHASISWA AKUNTANSI TERHADAP KONSEP DASAR AKUNTANSI (Analysis about Understanding Students Majoring In Accounting of the Basic Concepts of Accounting) - Elma Muncar Aditya (STIE Pelita Nusantara Semarang, 2011)
Purpose of this study was to improved empirically about differences of understanding and comprehension of students come from SMK majoring in accounting, IPS high schools and IPA high schools against of the basic concepts of accounting. The sample in this study are 32 students majoring in Accounting, S1 “X” University which is listed as an active second semester students for the academic year 20010/20101 and has completed the introductory course in accounting 1. This study uses Analysis of Variance (ANOVA) test to measure differences of understanding and comprehension of students come from SMK majoring in accounting, IPS high schools and IPA high schools of the basic concepts of accounting. Results showed that there is there is no significant difference of understanding and comprehension of the basic concepts of accounting between students come from IPA high Schools and IPS high schools (H1), significant difference of understanding and comprehension of the basic concepts of accounting between students come from SMK majoring in accounting and IPA high schools (H2), and significant difference of understanding and comprehension of the basic concepts of accounting between students come from SMK majoring in accounting and IPS high schools (H3).